PENGEMBANGAN MEDIA DIORAMA BERBASIS KONTEKSTUAL PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 1 LANGSA - Maulida Maulida; Tengku Muhammad Sahudra; Mufti Riyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Natural and Social Sciences (IPAS) learning in elementary schools is still dominated by the use of textbooks, making the learning process less engaging and causing students to be passive, particularly in understanding local cultural materials. This study aimed to develop contextual-based diorama learning media to improve the understanding of fifth-grade students at SD Negeri 1 Langsa. The research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, questionnaires, and pre-tests and post-tests. The results showed that the developed diorama media was highly feasible and effective, as indicated by the increase in students' average scores from 54 to 91. The paired t-test yielded a t-value of 15.573, exceeding the t-table value of 2.20099 (α = 0.05), indicating a significant improvement in learning outcomes. In addition, 90% of students gave very positive responses to the media, demonstrating its potential as an innovative learning resource in IPAS instruction. Keywords: Diorama Media, IPAS Learning, Contextual Learning